Temporary threshold shifts following monaural and binaural exposure to high frequency pure-tones - N, Shivashenkar (Journal of All India Institute of Speech and Hearing)
TTS at low frequ ncies following monaural and binaural exposures have revealed that, TTS following binaural exposures is less than the TTS following monaural exposures (Hirsh, 1958; Ward, 1965; Kerlovich et al., 1972 ; Kerlovich et al., 1974). This difference in TTS was explained on the basis of the middle ear muscles activity which is restricted to low frequencies only (below 2.KHz). During binaural exposure, the middle ear muscles contract more vigorously and reduce the energy reaching the cochlea, thereby there will be reduction in TTS during binaural exposures. In addition to th· acoustic reflex action Ward (1965) considers the ac·jonof olivo-cochlear bundle and cochleo-cochlear pathways to be present during binaural exposures at low frequencies. Dayal (1973) reports the ac· ion of crossed olivo-cochlear bundle (COCB) at high frequencies and revealed that, the COCB is not responsible for adaptation at high frequencies as he still could find some inhibitory responses even when COCB was cut. He assumes that, homolateral olivo-cochlear bundle may play a role in the adaptation mechanism at high frequencies